(3Pjd eQBI GdReGfs - (3ehSi Hf eMeO Hf CHj GdMSjf CMeO Gdjhfjfj GdHYdHcj, bWH GdOjf, CHh GdaJM , (B726 (3g` s; (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s ((3jYbhH Hf YHO GdMb Hf eMeO s)
(3ChdgG (B:s
(3GdSfI GdQGHYI hGdSJhf hSJeGFI , hONdJ gPg GdSfI hGdNdjaI hedhc GdWGhFa edi GdUhQI GdeSJbQI s
(3BNQgG (B:s
(3JQLeI eSYhO Hf YHO Gddg Hf YeQ GdLhjfi HbUjOI ef TYQg ai GdRgO ChdgG (B: (3ZQGe Edi GdCMHGH djS jMhd haQW GTJjGb fMhgf Whjd s
(3eLdO efg jHOC HMhGOK SfI (B664 (3g` hjfJgi HBNQ GdSfI (B5674s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs